2016
DOI: 10.1016/j.kjms.2016.11.001
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of mechanical strengths of three types of mini‐implants in artificial bones

Abstract: We investigates the effect of the anchor area on the mechanical strengths of infrazygomatic mini-implants. Thirty mini-implants were divided into three types based on the material and shape: Type A (titanium alloy, 2.0×12 mm), Type B (stainless steel, 2.0×12 mm), and Type C (titanium alloy, 2.0×11 mm).The mini-implants were inserted at 90° and 45° into the artificial bone to a depth of 7 mm, without predrilling. The mechanical strengths [insertion torque (IT), resonance frequency (RF), and removal torque (RT)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Considering that primary stability is one of the key factors for the clinical success of MIs [8,[10][11][12][13], its evaluation can be performed using methods such as periotest, pull-out and insertion/removal torque. It is defined as mechanical bone stability immediately after MI insertion [14][15][16][17] and it should be noted that cortical bone is an important factor in MI stability [11,14,15,17,18]. The present study observed that the primary stability of 12×2.0 mm steel MIs was superior to the other evaluated MIs.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…Considering that primary stability is one of the key factors for the clinical success of MIs [8,[10][11][12][13], its evaluation can be performed using methods such as periotest, pull-out and insertion/removal torque. It is defined as mechanical bone stability immediately after MI insertion [14][15][16][17] and it should be noted that cortical bone is an important factor in MI stability [11,14,15,17,18]. The present study observed that the primary stability of 12×2.0 mm steel MIs was superior to the other evaluated MIs.…”
Section: Discussionmentioning
confidence: 43%
“…In the present study, percussion test evaluation did not reveal significant differences among the groups evaluated. However, in the study by Tseng et al [17], 2.0×11 mm titanium MIs showed higher resonance values than 2.0×12 mm titanium MIs and 2.0×12 mm steel MIs.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…When considering the issue of the length of screws fixing the plates, it should be noted that the longer the screws used, the stronger they anchor in the bone and stabilize the osteosynthesis [31][32][33]. The longer the screw, the more stable the fixation, even for plateless osteosynthesis [34,35].…”
Section: Resultsmentioning
confidence: 99%